2018
DOI: 10.1016/j.socscimed.2017.03.058
|View full text |Cite
|
Sign up to set email alerts
|

The weight of racism: Vigilance and racial inequalities in weight-related measures

Abstract: In the United States, racial/ethnic inequalities in obesity are well-documented, particularly among women. Using the Chicago Community Adult Health Study, a probability-based sample in 2001–2003 (N=3,105), we examined the roles of discrimination and vigilance in racial inequalities in two weight-related measures, body mass index (BMI) and waist circumference (WC), viewed through a cultural racism lens. Cultural racism creates a social environment in which Black Americans bear the stigma burden of their racial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 67 publications
1
95
0
Order By: Relevance
“…UTBP simultaneously represents a threat to physical safety, freedom, financial wellbeing, sense of agency, and sense of self ( Harris, 2010 , Brunson, 2007 , Henning, 2017 ). One study, for instance, showed that exposure to racial discrimination was associated with increased body mass index (BMI) and waist circumference because those who experienced discrimination also experienced chronic vigilance ( Hicken, Lee, & Hing, 2017 ). This pattern may extend to exposure to UTBP as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UTBP simultaneously represents a threat to physical safety, freedom, financial wellbeing, sense of agency, and sense of self ( Harris, 2010 , Brunson, 2007 , Henning, 2017 ). One study, for instance, showed that exposure to racial discrimination was associated with increased body mass index (BMI) and waist circumference because those who experienced discrimination also experienced chronic vigilance ( Hicken, Lee, & Hing, 2017 ). This pattern may extend to exposure to UTBP as well.…”
Section: Introductionmentioning
confidence: 99%
“…Racial disparities in obesity-related outcomes including BMI and waist circumference are more pronounced among females ( Jackson et al, 2013 , Mensah et al, 2005 , Wang and Beydoun, 2007 ). Moreover, some research reports that exposure to stressors is more likely to result in increased BMI among females than males ( Hicken, Lee, & Hing, 2017 ). In this study, we test whether UTBP exposure partially accounts for black-white disparities in WC separately for women and men.…”
Section: Introductionmentioning
confidence: 99%
“…Several scholars have found support for the weathering hypothesis, as there is evidence of elevated allostatic load (a measure of chronic physiological stress) scores among Black adults, compared to whites, which likely contributes to Black-White health inequities. As it relates to frequent navigation of white spaces, Hicken and colleagues have found that when people's stress response is repeatedly activated due to apprehension over facing racism and discrimination (vigilance), dysfunction in the body's regular stress response system occurs [33][34][35]. Even if an act of discrimination is not perceived, Black people remain hyper-alert and prepared to confront any instance of intentional or unconscious racism.…”
Section: Chronic Stress and Healthmentioning
confidence: 99%
“…The sum of these efforts to "perform" is exhausting. Findings from multiple papers indicate that effort to maintain a public face exacts a toll on Black Americans and leads to burnout [33,35,54]. Respondents in qualitative investigations of upwardly mobile African Americans report feelings of anger, hurt, disappointment and even rage as they struggle to outpace hegemonic, negative stereotypes and fight for professional legitimacy within white settings [55].…”
Section: Navigating White Spacesmentioning
confidence: 99%
“…These discriminatory interactions can themselves change behavior, and can make ID-related interactions a location for anticipatory stress, or racism-related vigilance, which can take its own toll on health and well-being. 45 That is, above and beyond differences in ID acceptance, negative commentary can inhibit individuals from repeated use of their Washtenaw IDs, therefore, creating a racially biased system and enhancing community distrust of an equity-driven community intervention. Furthermore, the act of questioning government paperwork is a symbolic interaction often linked to the threat of deportation.…”
Section: Discussionmentioning
confidence: 99%